2012
DOI: 10.1016/j.neurobiolaging.2010.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Age-related effects on cortical thickness patterns of the Rhesus monkey brain

Abstract: The rhesus monkey is a useful model for examining age-related as well as other neurological and developmental effects on the brain, because of the extensive neuroanatomical homology to the human brain, the reduced occurrence of neurological diseases such as Alzheimer’s disease as well as the possibility of obtaining relevant behavioral data and post-mortem tissue for histological analyses. In this study, cortical thickness measurements based on a cortical surface modeling technique were applied for the first t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
38
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 48 publications
7
38
1
Order By: Relevance
“…For example, at the microscopic level, some studies have reported a reduction of synapses in the non-human primate neocortex and other areas (Peters et al 1998;Peters et al 2008;Hara et al 2011) while others have reported loss of spines and atrophy of dendrites (Dumitriu et al 2010;Dickstein et al 2007). At a more global level, several studies using MRI methods have reported age-related reductions in the thickness or volume of the cerebral cortex or hippocampus (Alexander et al 2008;Koo et al 2012;Shamy et al 2011), a finding compatible with Fig. 1 Matched levels of T1 MRI scans are shown for a 6-yearold young female monkey (a) and a 24-year-old female monkey (b) where there is obvious enlargement of the atrium of the lateral ventricle.…”
Section: Ultrastructural Observations Of Non-human Primate Cortex Witmentioning
confidence: 60%
“…For example, at the microscopic level, some studies have reported a reduction of synapses in the non-human primate neocortex and other areas (Peters et al 1998;Peters et al 2008;Hara et al 2011) while others have reported loss of spines and atrophy of dendrites (Dumitriu et al 2010;Dickstein et al 2007). At a more global level, several studies using MRI methods have reported age-related reductions in the thickness or volume of the cerebral cortex or hippocampus (Alexander et al 2008;Koo et al 2012;Shamy et al 2011), a finding compatible with Fig. 1 Matched levels of T1 MRI scans are shown for a 6-yearold young female monkey (a) and a 24-year-old female monkey (b) where there is obvious enlargement of the atrium of the lateral ventricle.…”
Section: Ultrastructural Observations Of Non-human Primate Cortex Witmentioning
confidence: 60%
“…The brains of the main animal models used in neuroprosthetic research pale in comparison. For example, the weight of the brain and surface area of the cerebral cortex range from 1.8 g and 6 cm 2 for the adult rat 12 to 90 g and 110 cm 2 for the rhesus monkey 13 . The topologies of the brain also differ widely: small mammals have smooth brain surfaces, whereas the brains of primates (including humans) display complex external topographies and patterns of convolution that result from gyrification of the cortical surface 14 (FIG.…”
Section: Understanding Neural Materials Macroscopic and Morphologicalmentioning
confidence: 99%
“…The cerebral cortex of humans -the outer, 2-3-mm-thick layer of grey matter over the brain hemispheres -is a highly convoluted structure, with more than half of its actual surface area hidden from the apparent, directly accessible outer brain surface. Typical sulci radii and gyri depths in the cortex of primates 13 are in the range of 1-5 mm. In the CNS, the cerebral and spinal tissues are protected by a multi-layered structure formed of meninges (that is, membranes including the pia mater, arachnoid mater and dura mater), bone, connective tissue and skin (FIG.…”
Section: Understanding Neural Materials Macroscopic and Morphologicalmentioning
confidence: 99%
“…In searching for the neurobiological basis of agerelated cognitive impairments, quantitative MRI has shown that though gray matter cortical thickness is reduced (Alexander et al 2006;Koo et al 2010), total gray matter volume is preserved (Wisco et al 2008) and histological studies of gray matter have shown that neurons are not lost with age (e.g., Merrill et al 2000;Peters et al 1998). In contrast, both MRI and histological studies in monkeys and humans have shown that white matter volume is lost with age (Albert 1993;Guttmann et al 1998;Peters and Rosene 2003;Tang et al 1997;Wisco et al 2008).…”
Section: Introductionmentioning
confidence: 99%